Evaluation of kidney status by ultrasonography in canines: an experimental study (Research in Agriculture Livestock and Fisheries, 2015)
Kidney is a major organ for homeostasis of the body's extracellular fluids by maintaining a constant internal environment. By playing such crucial responsibility kidney remains vulnerable for various diseases and disease condition. Other than laboratory findings, application of ultrasonography can be considered as one of the finest diagnostic tool to determine the architectural detail of kidney. To compare the study, we have taken two groups of canine, namely healthy and clinical. The later grouped was screened based on clinical signs, Blood Urea Nitrogen (BUN) and Serum Creatinine value. Sonography was performed by using Brightness mode instrument for both the groups. The values were analyzed by Prolate Ellipsoid formula to estimate the volume of kidney. There was significant variation in sizes between the kidneys of both the groups. Moreover, the size of the kidneys of few clinical cases, which has been suffering from renal disorder since long, reveals smaller size kidney than the healthy groups. Thus, this noninvasive method is quite practicable to evaluate the size of kidney amongst various renal failure cases. DOI: http://dx.doi.org/10.3329/ralf.v1i1.22373 Res. Agric., Livest. Fish.1(1): 105-108, Dec 2014